Enhancing Production of Pinene in Escherichia coli by Using a Combination of Tolerance, Evolution, and Modular Co-culture Engineering - Niu, Fu-Xing; He, Xin; Wu, Ya-Qin; Liu, Jian-Zhong (Frontiers in Microbiology, 2018)
α-Pinene is a natural and active monoterpene, which is widely used as a flavoring agent and in fragrances, pharmaceuticals, and biofuels. Although it has been successfully produced by genetically engineered microorganisms, the production level of pinene is much lower than that of hemiterpene (isoprene) and sesquiterpenes (farnesene) to date. We first improved pinene tolerance to 2.0% and pinene production by adaptive laboratory evolution after atmospheric and room temperature plasma (ARTP) mutagenesis and overexpression of the efflux pump to obtain the pinene tolerant strain Escherichia coli YZFP, which is resistant to fosmidomycin. Through error-prone PCR and DNA shuffling, we isolated an Abies grandis geranyl pyrophosphate synthase variant that outperformed the wild-type enzyme. To balance the expression of multiple genes, a tunable intergenic region (TIGR) was inserted between A. grandis GPPSD90G/L175P and Pinus taeda Pt1Q457L. In an effort to improve the production, an E. coli-E. coli modular co-culture system was engineered to modularize the heterologous mevalonate (MEV) pathway and the TIGR-mediated gene cluster of A. grandis GPPSD90G/L175P and P. taeda Pt1Q457L. Specifically, the MEV pathway and the TIGR-mediated gene cluster were integrated into the chromosome of the pinene tolerance strain E. coli YZFP and then evolved to a higher gene copy number by chemically induced chromosomal evolution, respectively. The best E. coli-E. coli co-culture system of fermentation was found to improve pinene production by 1.9-fold compared to the mono-culture approach. The E. coli-E. coli modular co-culture system of whole-cell biocatalysis further improved pinene production to 166.5 mg/L.